Analisis Kemampuan Numerasi Siswa dalam Menyelesaikan Soal AKM Konten Bilangan Ditinjau dari Kemampuan Awal Matematika - Yuliastuti, Nia Dwi; Fathurrohman, Maman; Fatah, Abdul (Himpunan: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2025)
This research is motivated by the low numeracy skills of students at SMPN Satu Atap Curug Serang City, this is supported by the results of the Education Report Card issued by the Ministry of Education and Culture where the number content is the lowest and needs special intervention. The low numeracy skills are influenced by the low initial math skills of students. The purpose of this study is to describe students' numeracy skills in solving AKM-type problems based on high, medium, and low initial math skills. The research method used is descriptive qualitative by conducting tests and interviews. The research subjects were classes VII and VIII as many as 76 students, then grouped based on high, medium and low initial mathematical abilities, then six students were selected as representatives to be interviewed. The instruments in this study included a test of initial math ability, a numeracy test and an interview.Based on the results showed that, students with high initial mathematical ability amounted to 9 students out of 76 students were very able to apply precisely the three indicators of numeracy skills. Students with medium initial mathematical ability amounted to 26 students out of 76 students were quite capable in applying the three indicators of numeracy skills. Students with low initial math ability amounted to 41 students out of 76 students have not been able to apply the three indicators of numeracy skills.